Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Keterampilan Menulis Puisi Di Sekolah Dasar - Lia Marlani; Anggi Giri Prawiyogi (Al-Aulad: Journal of Islamic Primary Education, 2019)
The background of this research is the low writing ability of students especially on poetry writing ability. This research was conducted in grade V, SDIT Cendikia. Learning model applied is model of Project Based Learning. The research method used in this research is Classroom Action Research. The research consisted of three cycles each. The purpose of this research is to know the activity and result of student learning on poetry writing ability, after applied of Project Based Learning model. Research data obtained through observation and test. From the results of this research can be concluded that the implementation of the of Project Based Learning model can improve the ability of writing poetry in class V. The results showed that the ability to write poetry can be increased, can be seen from the results of student learning completeness on the initial test students who meet the KKM as much as 2 people, then the second is 6 people, and the third cycle is 9 people, and 14 people on the third cycle of the number of students as many as 15 people. Therefore, students learning outcomes on writing poetry ability at the end of each cycle I to III have improved considerably. Based on the invention, it is suggested that the teacher can apply the learning of Project Based Learningamodel to improve poetry writing ability, as well as on other language ability.